MEDIA AND PHILOSOPHY: SEARCH FOR PROBLEMS - Isayeva, Dilbar Abdukadirovna (Innovative Development in Educational Activities, 2023)
This article deals with the problems of the media, which are an important and fundamental part of the media environment that permeates the entire social space. Through the definition of habitus and the gradual transition to social space, it was possible to outline a certain kind of media environment and those mechanisms that, through the media, generate certain problems in people’s heads.